Laju Tangkap dan Analisis Usaha Penangkapan Lobster (Panulirus Sp) Dengan Jaring Lobster (Gillnet Monofilament) di Perairan Kabupaten Kebumen - Boesono, Herry; Anggoro, Sutrisno; Bambang, Aziz Nur (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
Crayfish (Spiny lobsters, Panulirus sp), including marine fishery commodities which have an important role as an export commodity of the kind of crustaceans (Crustacea) after shrimp Penaeid. Efforts continue to increase utilization will threaten the sustainability of the resource, if not attempted control measures. The purpose of this study was to determine the level of the catch rate of lobster resources in the District Kebumen and to analyze the financial aspects, the amount of capital, revenue, and profit from lobster fishing effort in waters Kebumen district. The method used is descriptive method, where sampling by using purposive sampling method with a sample of 64 units ship. The research concluded that the value average size of the catch per unit arrests during the period 2004 until 2009 is 1,037914609 kg / trip. Financial analysis of lobster fishing effort using nets lobster fishing gear (gillnet monofilament) got the R / C ratio of lobster fishing effort has a value of R / C > 1 is 1,61, which means that lobster fishing effort it deserves. The calculation of earnings lobster fishing effort of 1,08, which means that lobster fishing effort carried out efficiently. Payback Period (PP) in lobster fishing effort in lobster fishing gear nets (gillnet monofilament) amounted to 0,92 years or 9 months, which means that fishermen can return all venture capital in less than1 year. Keywords : Spiny lobster (Panulirus sp), Catch Rate (Gillnet monofilament)